Insulin-like growth factor-1 levels are associated with interventricular septal thickening - Chen, Yuan; Cheng, Xinchun; Li, Suli; Yin, Yuting; Xing, Shuqing; Guo, Yanying (Frontiers in Endocrinology, 2022)
Background and Objective: Insulin-like growth factor-1 (IGF-1) regulates cardiomyocyte survival, hypertrophy and ageing. We aimed to investigate the potential correlation between IGF-1 and interventricular septal (IVS) thickening. Methods: Medical records data were obtained from the patients hospitalized between May 1, 2012, and April 31, 2022. All patients underwent echocardiography and had laboratory data on plasma IGF-1. We analysed the relationship between IGF-1 levels and IVS thickening based on logistic regression models. Results: The propensity score matching at a 1:4 ratio was performed for 180 patients with IVS thickening and 1964 patients without IVS thickening. Finally, 180 (case group) and 623 (control group) patients were enrolled. Of the total 803 patients, the mean age was 59 years and 59.7% were male. In multivariate-adjusted models that adjusted for propensity scores, the risk of IVS thickening increased with increasing in IGF-1 levels; specifically, the risk of IVS thickening increased per 1 ng/mL (OR 1.003, 95% CI: 1.002–1.004; P<0.001), per 5 ng/mL (OR, 1.016; 95% CI, 1.010–1.022; P<0.001) and 10 ng/mL (OR, 1.032; 95% CI, 1.019–1.045; P<0.001) increase in IGF-1 levels. When IGF-1 levels were expressed as a categorical variable, increased levels of IGF-1 led to an increased risk of IVS thickening; specifically, the OR of IVS thickening for T3>152.00 ng/mL was 2.020 (95% CI: 1.310–3.115, P< 0.01) compared to T1<102.00 ng/mL. We performed restricted cubic splines, and it showed a linear association between IGF-1 levels and the risk of IVS thickening. In splines for the age and sex subgroups, different IGF-1 levels increased the risk of IVS thickening among different age groups in males: 18–44 years when IGF-1 value>164.00 ng/mL, 45–60 years when IGF-1 value > 140.34 ng/mL and ≥60 years when IGF-1 value>108.20 ng/mL. In females aged 45–60 years, the risk of IVS thickening increased when IGF-1 levels were>207.45 ng/mL. However, IGF-1 was not significantly correlated with IVS thickening in females aged 18–45 and ≥60 years. Sensitivity analysis by excluding those with acromegaly did not change the relationship between IGF-1 and the risk of IVS thickening. Conclusion: Plasma IGF-1 levels were related to the risk of IVS thickening irrespective of blood pressure.